Analisis Kesulitan Siswa dalam Pembelajaran Matematika pada Materi Pecahan di Kelas III SDN 195 Palembang - Salsabilah Erika Putri; Nora Surmilasari; Ali Fakhrudin (Departement of Mathematics Education, 2023)
This study aims to determine the implementation of learning mathematics on fractional material, to find out students' difficulties in learning mathematics on fractional material, and to find out efforts to overcome students' difficulties in learning mathematics on fractional material in class III SDN 195 Palembang. This type of research is a qualitative descriptive research. The research subjects were students who had learning difficulties in class III at SDN 195 Palembang. Data collection techniques used are observation, interview and documentation methods. The research instruments used were observation, interviews and documentation. The results of this study indicate that (1) the implementation of learning mathematics on fractional material, the method used is still not varied, namely the lecture method and does not involve students being physically involved in learning, and the facilities and infrastructure are still inadequate, (2) students' difficulties in learning mathematics on fractional material that includes internal and external factors.